RETRACTED: Yang et al. How Does Physical Activity Enhance the Subjective Well-Being of University Students? A Chain Mediation of Cognitive Reappraisal and Resilience. Behav. Sci. 2024, 14, 164 - Mengmeng Yang; Ji Wu; Yigang Wu; Xinxing Li (Behavioral Sciences)
The journal Behavioral Sciences retracts the article titled, “How Does Physical Activity Enhance the Subjective Well-Being of University Students [...]